Planck`S Dual Angular - Momentum As Gravity & Antigravity Waves - Georgallides, Markos (European Journal of Applied Sciences, 2024)
The Interactions: One of the most important concept in Geometry is, distance, which is the Quanta in geometry, while in Material-Geometry the composition of Opposite, the Material-Point which is the Quanta in Chemistry and Physics. As in Algebra Zero, 0, is the Master-key number for all Positive and Negative numbers and this because their sum and multiplication becomes zero, and the same on any coordinate-System where ± axes pass from zero, The Rolling of Positive ⊕, constituent on the Negative ⊝, constituent, creates the Neutral Material Point which Equilibrium. Angular-Momentum is identical with Spin and consists the First-Discrete-Energy-Monad which occupies, Discrete Value and Direction, in contradiction to the Point which is Nothing, Dimensionless and without any Direction. Quaternion [(+) ↻↺ (-)] ≡ Box BR which carries the Principal stress σ between A (+), B (-) which σ, as Centripetal-acceleration is the minimum Energy becoming from the in-storage AB acceleration and is equal to the Gravity g. Because of the two different motions, Revolving and Periodic, acceleration of the Gravity g ≡  σ exists as the First Energy-Box-BR , while in the Second BP is followed the Local-Extreme-case this acceleration of Gravity g ≡  σ, is altered Locally by changing the Principal-stress σ with an Local-uniform-Pressure → gL ≡ g k = g. [Force/Area] = G, i.e. The minimum Local - Energy acceleration is the known, Universal Gravitational-constant G = g k = kE g = kL σ, for Macrocosm and Microcosm, Obeying Newton`s Laws of motion. It was proved that, Constant G, is the mechanism for the First-kick-Start on the Granular-Energy-monad, g, which Acts in the lightest and less-mass Particle and which is the Hydrogen. The Electron- Nutation-Energy due to g, effect is the minimum frequency f N ≡ fR = 2, 8398447.1010 s −1 , and which so exists in all Atoms. This Energy in Hydrogen-Cave as E-M, Conductor ≡ The Pin of Atom-Plug Into their Sockets, which are the Orbit – Bracket – Hooks ≡ The Hands of Atoms, i.e. → The Atoms Plug with their Pins into the other Atoms-Drains = Holes, and so are Bonded. This is the Resonance frequency between all Atoms, and because Hydrogen is Common to all Atoms, so Bond to Molecules and Crystals, and all other Compounds in this Cosmos.